The The eruption phase of second permanent molar in children aged 11-15 years in coastal area of pugerIndonesia - Probosari, Niken; Berlian Prihatiningrum; Mulyani, Sri; ., Sulistiyani; Setyorini, Dyah; Budi Rahardjo, Roedy; ., Sukanto (Journal of Oral and Dental Sciences, 2024)
Background : The first permanent teeth that erupt in the oral cavity is the first permanent molar, which has a high risk of extraction due to caries. Functionally, permanent second molars can replace the function of permanent first molars. Permanent second molars erupt at the age of 11-15 years. The eruption of teeth can be influenced by environmental factors. One of the environmental factors is the geographical conditions. Geographical conditions, such as in coastal areas, will affect the economic conditions and consumption patterns of people living in the area, so it is possible that this can affect tooth eruption. Aims and Objectives : This study aimed to examine the eruption phase of the second permanent molar in children aged 11-15 in the coastal Puger district, Jember. Study Design : This study is a descriptive observational study with a cross-sectional approach. Materials and Methods: The sample was 100 pairs of study models of children aged 11-15 years who lived on the coastal area of Puger. Results : Observed eruption phase of permanent second molars in maxillary and mandibular study models and classified into four phases: 0.00 = tooth not erupted, 0.25 = cusp erupted until quarter of the height of the tooth is erupted, 0.50 = half of the height of the tooth is erupted, 1.00 = tooth has more than half until the whole clinical crown erupted. Conclusion : The results showed that the children on the Puger coast had a faster eruption time, in addition, the mandibular teeth erupted earlier than the maxillary teeth and needed 3 years to reach full eruption.